The Effects of Oral Semaglutide on Hepatic Fibrosis in Subjects with Type 2 Diabetes in Real-World Clinical Practice: A Post Hoc Analysis of the Sapporo-Oral SEMA Study - Hiroya Kitsunai; Yuka Shinozaki; Sho Furusawa; Naoyuki Kitao; Miki Ito; Hiroyoshi Kurihara; Chiho Oba-Yamamoto; Jun Takeuchi; Akinobu Nakamura; Yumi Takiyama; Hiroshi Nomoto (Pharmaceuticals)
Background/Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD) is an important common comorbidity in subjects with type 2 diabetes, and liver fibrosis is a factor directly related to its prognosis. Glucagon-like peptide-1 receptor agonists are useful treatment options for MASLD; however, the efficacy of oral semaglutide in treating liver steatosis/fibrosis has not been fully elucidated. Methods: A secondary analysis of a multicenter, retrospective, observational study investigating the efficacy and safety of oral semaglutide in Japanese subjects with type 2 diabetes in a real-world clinical setting (the Sapporo-Oral SEMA study) was conducted. Subjects in the original cohort were divided into groups as follows: subjects with suspected MASLD (alanine aminotransferase > 30 U/L) were placed in an overall group; a subpopulation from an overall group at high risk for hepatic fibrosis (fibrosis-4 (FIB-4) index ≥ 1.3 or platelet count < 200,000/µL) was placed in a high-risk group; and the remaining subjects were placed in a low-risk group. Changes in the hepatic steatosis index and FIB-4 index after oral semaglutide induction were explored using a paired t-test or the Wilcoxon signed-rank test. Results: Overall, 169 subjects (including 131 that switched from other medications) were analyzed, and 67 and 102 subjects were selected for the high-risk and low-risk groups, respectively. Oral semaglutide significantly improved the hepatic steatosis index (from 46.1 to 44.6, p < 0.001) and FIB-4 index (from 1.04 to 0.96, p < 0.001) as well as several metabolic parameters in all cohorts. The efficacy of semaglutide in treating liver fibrosis was confirmed by the addition of, and switching from, existing agent groups. Furthermore, improvement in the FIB-4 index was significantly negatively correlated with the baseline FIB-4 index. Conclusions: The induction of oral semaglutide might be a useful treatment option for subjects with type 2 diabetes at high risk for liver fibrosis, even when switching from conventional medications for diabetes.